THE INFLUENCE OF WORKER STATUS, COMPETENCE AND WORK CULTURE ON EMPLOYEE PERFORMANCE PT SUMMIT OTO FINANCE SURABAYA - Ronggot, Marianus; Jannah S, Miftahul (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study aims to determine whether the variables of worker status (X1), employee competence (X2) and organizational culture (X3) simultaneously have a significant effect on employee performance (Y) PT Summit Oto Finance Surabaya.Data collection techniques are carried out through questionnaires, inter-views, and observation techniques, which consist of primary data and secondary data. Furthermore, the data was analyzed quantitatively, namely by using a statistical model in the SPSS 22.00 program, with descriptive analysis techniques and multiple linear regression analysis. The results showed that: There is a joint (simultaneous) influence of independent variables (X) in the form of worker status (X1), compe-tence (X2) and organizational culture (X3) on the dependent variable (Y), namely employee performance at the warehouse of PT Summit Oto Finance Surabaya, Based on the results of the t test calculations car-ried out, it can be seen that the independent variables (X) in the form of worker status (X1), competence (X2) and organizational culture (X3) partially have a significant effect on the dependent variable (Y), namely employee performance at the warehouse of PT Summit Oto Finance Surabaya.